If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = 6g + -3 Reorder the terms: -15 = -3 + 6g Solving -15 = -3 + 6g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-6g' to each side of the equation. -15 + -6g = -3 + 6g + -6g Combine like terms: 6g + -6g = 0 -15 + -6g = -3 + 0 -15 + -6g = -3 Add '15' to each side of the equation. -15 + 15 + -6g = -3 + 15 Combine like terms: -15 + 15 = 0 0 + -6g = -3 + 15 -6g = -3 + 15 Combine like terms: -3 + 15 = 12 -6g = 12 Divide each side by '-6'. g = -2 Simplifying g = -2
| 50x+3=7 | | 42=6x+7 | | x/3-2=5 | | 4(q-5)=16 | | 8a+10b=6 | | 2Y^2+9Y-5= | | 4y=208-6x | | x^3-6x^2+16X=96 | | 2(3x-4)=28 | | 0.5x-1.5=2.5 | | 5.4+-3(4m+3)=45.7 | | 6x+14x=16 | | 2(3x+7)-(x-4)= | | -6y+15=-9 | | -6+3y/5=3 | | -2(5)+2=5y-1 | | 3(4y-7)=6 | | 8(x+3)=10(x+7) | | (-2)(-7)=14 | | 9(5x-2)=17 | | 2a/5+5=1 | | (6x+2)+(4x+8)= | | k/5-6=2 | | 2-3c=-7 | | 8x=10-11x | | 2n/3+5=7 | | 7x+2=20+3x+8 | | 12-x=16 | | -7-x=5 | | 2(n-5)=4-2(7-n) | | 2(x+2)=34 | | x^4-5x^2+2=0 |